Programme Development Of A Degree In A Halal Administration: Experience In Curriculum Design In University Malaysia Pahang - Hasan, Ahmad; Abd Jalil, Borham (2010)
Halal (a term refers to Islamic religious permission of use of goods and services) has become a global awareness in the last decade including in the non-muslim countries. Business transaction of halal products has grown rapidly and the latest figure shows the halal business value reaches USD1.7 trillion in 2009 around the globe. As more and more industry players involve in halal business, the need for qualified people to administer the halal matters tops the priority. Halal consultancy, research and commercialization are keys to successful halal business. Apparently, there is a critical shortage of qualified people who can work in the halal industries. UMP has taken a maiden step to develop such academic qualification to fulfill these vacancies. The paper will share experience in the curriculum design for Bachelor of Science in Halal Administration in the UMP. Focus is mainly given to discussions on the subject mapping, process flow, regulations stipulated by the Malaysian Qualification Agency (MQA) and views from the university’s senate. Special attention is also drawn to the market survey, the establishment of Board of Studies as well as Expert Panels for the program. Even though most of the development processes meet the standard, the most critical part lies in the contents of each subjects offered and the marketability of graduates produced.